2020
DOI: 10.3390/ijerph17062129
|View full text |Cite
|
Sign up to set email alerts
|

Well-Being, Obesity and Motricity Observatory in Childhood and Youth (WOMO): A Study Protocol

Abstract: Background: Childhood obesity is one of the greatest public health problems facing advanced societies, and Spain is one of the countries with the highest incidence. There are many studies that monitor at the national level, but given the lack of specificity, lack of updating and scarcity of epidemiological data on overweight, obesity, physical condition and well-being of children and adolescents in Extremadura, it seems necessary to create a Well-being, Obesity and Motricity Observatory in Childhood and Youth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 67 publications
0
12
0
1
Order By: Relevance
“…In this project, a variety of tools were used to assess physical condition and body composition. We followed the procedures proposed in the study protocol WOMO [8], which allowed controlled outcomes associated with monitoring overweightness and obesity, as well as the lifestyles of children and adolescents.…”
Section: Procedures and Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…In this project, a variety of tools were used to assess physical condition and body composition. We followed the procedures proposed in the study protocol WOMO [8], which allowed controlled outcomes associated with monitoring overweightness and obesity, as well as the lifestyles of children and adolescents.…”
Section: Procedures and Measuresmentioning
confidence: 99%
“…Due to the lack of specificity, the need for continuous updating, and the scarcity of epidemiological data on overweightness, obesity, and physical fitness, an observatory named the Well-Being, Obesity, and Motricity Observatory in Childhood and Youth (WOMO) was created, to monitor the weight and fitness status of children and adolescents, knowing their lifestyles, and developing or proposing different strategies to combat and prevent this problem. Specifically, it was created to evaluate the 10- to 17-year-old population due to the lack of data [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Spain is one of the countries with the highest incidence of overweight and obesity in the world (Wijnhoven et al, 2014). The Spanish National Health Survey (SNHS), reporting data of children and adolescents aged between 2 and 17 years, determined that the percentage of overweight (body mass index) and obesity in Spain was 28.6% (Mendoza-Muñoz et al, 2020). For this reason, it has become one of the greatest challenges for public health in the 21st century because it represents a high cost for the healthcare system (Ortega, Ruiz & Castillo, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, adolescence is a crucial stage towards a healthy lifestyle because puberty is a key period for skeletal mineralization and obesity prevention (Smith et al, 2014). In addition, recent studies have shown an increasing trend of adolescents towards a sedentary lifestyle, considering it as the disease of the 21st century (Mendoza-Muñoz et al, 2020), and suggesting that the recommended levels of physical exercise are not achieved (García-Hermoso, Ramírez-Vélez & Saavedra, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, adolescence is a crucial stage towards a healthy lifestyle because puberty is a key period for skeletal mineralization and obesity prevention (Smith et al, 2014). In addition, recent studies have shown an increasing trend of adolescents towards a sedentary lifestyle, considering it as the disease of the 21 st century (Mendoza-Muñoz et al, 2020), and suggesting that the recommended levels of physical exercise are not achieved (García-Hermoso, Ramírez-Vélez & Saavedra, 2019).…”
Section: Introductionmentioning
confidence: 99%